The potassium channel KCNJ13 is essential for smooth muscle cytoskeletal organization during mouse tracheal tubulogenesis - Wenguang Yin (Nature Portfolio, 2018)
Tubulogenesis is required for the formation of many internal structures including the trachea. Here, the authors show that the potassium channel KCNJ13 regulates tracheal tube formation, with shorter tracheas forming in mutant mice due in part to changes in actin organization in tracheal smooth muscle cells.